Farm Inefficiency As Rational Equilibrium: Rethinking Agricultural Household Behavior Beyond Production Functions - Muhammad Fauzan (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Farm efficiency is commonly evaluated through frontier-based metrics, with deviations from the production frontier often interpreted as evidence of suboptimal farmer behavior. This paper challenges that interpretation by arguing that measured farm inefficiency in smallholder agriculture may reflect rational equilibrium under constrained household optimization rather than technical failure alone. Using a structured conceptual literature review, the study synthesizes literature on technical efficiency, stochastic frontier analysis, data envelopment analysis, metafrontier approaches, agricultural household models, non-separability, risk, labor allocation, and smallholder decision-making. The analysis shows that production decisions in smallholder systems are rarely separable from household consumption, labor allocation, liquidity management, and risk exposure. Under incomplete markets, endogenous shadow wages, heterogeneous technologies, and pervasive uncertainty, farmers may rationally choose conservative input use, diversification, partial technology adoption, or lower production intensity to protect household welfare. These choices may appear inefficient from a production-centered perspective, yet they can be consistent with broader household objectives such as income stability, consumption smoothing, labor feasibility, and livelihood security. The paper contributes conceptually by reframing farm inefficiency as a possible rational equilibrium outcome and by shifting the analytical benchmark from proximity to a production frontier toward coherence between household objectives, constraints, and observed choices. This reinterpretation has implications for future research and policy, suggesting that frontier estimates should be complemented with household-level variables and used as diagnostic tools rather than final judgments of farmer performance.